Neutrophils as main players of immune response towards nondegradable nanoparticles - Bilyy, Rostyslav; Bila, Galyna; Vishchur, Oleg; Vovk, Volodymyr; Herrmann, Martin (Nanomaterials, 2020)
Many nano/microparticles (n/µP), to which our body is exposed, have no physiological way of removal. Our immune system sense these “small particulate objects”, and tries to decrease their harmfulness. Since oxidation, phagocytosis and other methods of degradation do not work with small, chemically resistant, and hydrophobic nanoparticles (nP). This applies to soot from air pollution, nano-diamonds from cosmic impact, polishing and related machines, synthetic polymers, and dietary n/µP. Our body tries to separate these from the surrounding tissue using aggregates from neutrophil extracellular traps (NETs). This effectively works in soft tissues where n/µP are entrapped into granuloma-like structures and isolated. The interactions of hydrophobic nanocrystals with circulating or ductal patrolling neutrophils and the consequent formation of occlusive aggregated NETs (aggNETs) are prone to obstruct capillaries, bile ducts in gallbladder and liver, and many more tubular structures. This may cause serious health problems and often fatality. Here we describe how specific size and surface properties of n/µP can activate neutrophils and lead to aggregation-related pathologies. We discuss “natural” sources of n/µP and those tightly connected to unhealthy diets.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Nano/microparticles (nµP); Nanoparticle (nP); NETs; Neutrophil; Plasma membrane; Tubular structures